Contra-(Λ, sp)-continuity and δ(Λ, sp)-closed sets (European Journal of Pure and Applied Mathematics, 2022)
This paper deals with the concepts of upper and lower contra-(Λ, sp)-continuous multifunctions. Moreover, some characterizations of upper and lower contra-(Λ, sp)-continuous multifunctions are investigated.
Keywords: $δ(Λ,sp)$-closed set; upper contra-$(Λ,sp)$-continuous multifunction; lower contra-$(Λ,sp)$-continuous multifunction